Comparison of Chitosan Characterization from Mussel Shell Waste Using Varying Concentration of Solvents - Nur Maulida Safitri; Andi Rahmad Rahim; Ummul Firmani (Kontribusia : Research Dissemination for Community Development, 2021)
Massive amounts of mussel shell waste are generated and wasted from the aquaculture processing sectors, resulting in environmental pollution. This material contains chitosan as a valuable compound characterized as a non-toxic structural component with several food processing applications or medicinal applications. In this research, mussel shells were processed using different solvents concentrations in several stages: demineralization, deproteination, decolourization, and deacetylation. Our result showed that the C2 samples gained a high degree of deacetylation (31.8±0.21%) with low moisture and ash content and medium weight of yield. Further research is recommended to purify chitosan using various instrumentation and assess its bioactivity.